PENERAPAN BASIC LIFE SUPPORT PADA MASYARAKAT DALAM MENGHADAP BENCANA DI DESA LEKOMPANCING KEC. TANRALILI SULAWESI SELATAN - Irmayani Irmayani; Faisal Asdar; Andi Fajriansi; Nurafriani Nurafriani (Nusantara Hasana Journal, 2022)
Basic life support is one of the efforts that must be immediately carried out by a person if he find a victim who a disaster occurs, all activities will be carried out ini an emergency situation under chaotic conditions, so planning, coordination and good training are handling and evacuation when a disaster occurs is going well. The purpose of this activity is to contribute through the implementation of nursing related to emergencies in terms of natural disasters both before the disaster. The implementation method is conducting basic life support training for the community in dealing with disaster. The results of the evaluation after taining 80% of participants were able to explain and simulate initial handling during a disaster, basic life support simulation in the event of a disaster.